Phenotypic and genotypic screening of Bacillus cereus local isolates for their antimicrobial resistance - IZZADINI FARHANI; RATIH DEWANTI-HARIYADI; HANIFAH NURYANI LIOE (Society for Indonesian Biodiversity, 2024)
Abstract. Farhani I, Dewanti-Hariyadi R, Lioe HN. 2024. Phenotypic and genotypic screening of Bacillus cereus local isolates for their antimicrobial resistance. Biodiversitas 25: 4507-4514. Bacillus cereus is a sporeformer bacterium that ranks second as Indonesia's most common cause of foodborne illnesses from 2000 to 2015. The bacterium produces cereulides and enterotoxins, which trigger emetic and diarrheal syndromes. The rise of antibiotic resistance in pathogens such as B. cereus could complicate treatment and allow the bacterium to act as the reservoir of antibiotic-resistant genes. Currently, antibiotic resistance in B. cereus has not been reported in Indonesia. This study aims to evaluate the antibiotic resistance of 21 B. cereus local isolates obtained from foods against eight different antibiotics. The phenotypic resistance was evaluated using the Kirby-Bauer disc diffusion method, while resistance genes were detected using a polymerase chain reaction targeting the bla1, tetL, and tetB genes. None of the isolates (0%; 0/21) showed resistance to chloramphenicol, ciprofloxacin, or erythromycin. However, all (100%; 21/21) were resistant to ampicillin, cefoxitin, cephalothin, and penicillin G. Additionally, 4.8% (1/21) were susceptible to erythromycin, while 33.3% (7/21) were resistant to tetracycline. The detection of resistance-encoding genes revealed that 100% (21/21) of the isolates possessed the bla1 gene, but tetL and tetB genes were absent in any of the isolates (0%; 0/21).